Implementing integrated river basin management: lessons from the Red River Basin, Vietnam - Molle, Francois; Hoanh, Chu Thai (International Water Management Institute, 2009)
The report focuses on the establishment of the Red River Basin Organization (RRBO) in Vietnam, but expands its analysis to the wider transformations of the water sector that impinge on the formation and effectiveness of this organization. A few reflections on the policy process are drawn from this analysis, albeit in a tentative form given the relatively limited period of time considered here. The report shows that the promotion of IWRM icons such as RBOs by donors has been quite disconnected from the existing institutional framework. However, the establishment of RBOs might eventually strengthen a better separation of operation and regulation roles. Institutional change is shown to result from the interaction between endogenous processes and external pressures, in ways that are barely predictable.